PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVISTIGATION (GI) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IVD SD NEGERI 42 PEKANBARU - Hanisda, Henny Eka; Marhadi, Hendri; N, Lazim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study is classroom action research that aims to improve learning outcomes .Penelitian IPS was conducted on April 11 until April 21 .Subjek this research is class IVD SD Negeri 42 Pekanbaru with the number of children 38. Data collection techniques by observation and tests .Penelitian consists of 2 cycles. The data of this study learning outcomes of students has increased, where before conducting the investigation 38 students in the classical as many as 15 students (39.97%) completed the study while as many as 23 students (60.52%) is still not completed and still learning KKM below. After the act of Cooperative Learning Model Type Group Investigation (GI) .Aktivitas teachers in the first cycle categorized both increased with an average 79.15% and 89.83% in the second cycle with very good categories increased by 10.68%. Activities of students during the learning (Cycle I and Cycle II) categorized either by 75% in the first cycle and 88.35% in the second cycle with very good category, an increase of 13.35%. It can be concluded that the hypothesis is if implemented model of Cooperative Learning type Group Investigation (GI) can improve learning outcomes IPS IVD grade students of SD Negeri 42 Pekanbaru.Keywords: Cooperative Learning Model Group Investigation (GI), IPS Learning Outcomes